REMOTE WORKING AND COVID-19: DETERMINANTS OF PRODUCTIVITY OUTPUT IN SERVICE FIRMS - Oluyemi Theophilus Adeosun; Waliu Mulero Adegbite; Temitope J. Owolabi (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
The covid-19 pandemic has greatly impacted business operations, economic activities, working structures, and employee productivity globally. This has led to carefully thought out measures and panic-triggered guidelines to limit the virus's spread. This paper aims to examine key determinants of productivity in the service firms during the pandemic and how these factors could be sustained after the lockdown for optimal productivity. Using primary data collected from a questionnaire administered to 411 workers, a binary logistic regression was conducted to ascertain whether these determinants are of significance or not. The empirical results revealed that remote working would only be productive in service firms if working tools are available to workers; thus, productivity can be measured regularly irrespective of the worker's location. This paper responds to the need to evaluate the drivers of employee productivity during remote working, especially during the lockdown, and to understand better these drivers for organizations planning after the pandemic.